WACANA MELIHAT ALLAH DALAM TAFSIR TEOLOGIS: (STUDI KOMPARATIF TAFSIR AZ-ZAMAKHSYARI, IBN KATSIR DAN ASY-SYAUKANI) - Abdul Rohman (STAI Asy-Syukriyyah, 2022)
The purpose of this article is to compare the interpretations of Az-Zamakhsyari, Ibn Kathir, and Ash-Syaukani regarding the verse about the discourse of seeing Allah in the Koran. The problem raised is about how to interpret the ru'yatullah verse according to Az-Zamakhsyari, Ibn Kathir, and Asy-Syaukani and how the differences exist in the three interpretations. The research method used is the comparation interpretation method. The results obtained are that Az-Zamakhsyari has the view that Allah will not be seen by human eyes both in this world and in the hereafter. Meanwhile, Ibn Kathir and Ash-Syaukani argue that Allah will be seen by the eyes of believers in the days and the difference between the three interpretations is the difference in substance. The reason for the difference is that the reference sources used by each interpreter are the same. Az-Zamakhsyari refers only to linguistic studies and mu'tazilah theology, while Ibn Kathir and Asy-Syaukani refer only to verses of the Koran, linguistic studies, and the hadiths of the Prophet Muhammad.